DIKLAT PENGEMBANGAN KAPASITAS KOMPETENSI GURU SD DAN SMP DILINGKUNGAN DINAS PENDIDIKAN KABUPATEN LANGKAT - Darmawati Darmawati; Zainuddin Zainuddin; Khairtati Purnama Nasution; Lilik Hidayat Pulungan (Jurnal Pengabdian Mitra Masyarakat, 2023)
Education is the spearhead of the success of education in Indonesia, this is in accordance with the direction of the President of the Republic of Indonesia, that development for the next 5 years will prioritize the development of Indonesian human resources, one of which is educators/teachers. The results of the Teacher Competency Test still show that many teachers in Indonesia do not yet have the minimum competencies needed to facilitate quality learning. This condition motivated the Langkat District Education Office to work together with Permata Phsyco Consultant to collaborate in an effort to improve the quality of teacher resources through competence mastery of public elementary and junior high school teachers. The capacity and competency development training activities for public elementary and junior high school teachers within the Langkat District Education Office were attended by 1,200 participants. The material provided is Pedagogic Professional Competence and Personality Social Competence, this is in accordance with the provisions of UURI Number 14 of 2005 concerning Teachers and Lecturers. Based on the results of the reflections carried out by each resource person from the material components of the activity, the results of the participant's portfolio through reflection at the end of the activity, obtained an  adequate result of 79.03. While the results of the activeness of the participants as measured by willingness to ask questions, brainstorming, courage to go ahead and others reached a value of 85.25. This means that the participants are active carefully with full attention to the entire series of material provided by the resource person so as to obtain satisfactory results.